2009
DOI: 10.1021/ef900590b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Main Regularities of Biomass Liquefaction with Alcoholic Solvents

Abstract: The effects of three alcoholic solvents, including monohydric n-octanol, dihydric ethylene glycol, and trihydric glycerol, on the process of biomass liquefaction were studied by thermogravimetry (TG) analysis. The results showed that there were three stages during biomass liquefaction, including biomass dehydration, volatilization of alcoholic solvents, and biomass alcoholysis. At the stage of biomass alcoholysis, alcoholic solvents combined with fragments from biomass cracking, which resulted in exothermic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 21 publications
0
37
1
4
Order By: Relevance
“…Thus, at shorter times (3-7 min), the increase in conversion yield is mainly due to the fact that degradation/decomposition outweighs repolymerization. Then, with the prolongation of reaction time (9-11 min), degradation gradually decreased and repolymerization played the main role in liquefaction (Balat 2008;Zou et al 2009;Xie et al 2014), which attributed to the decrease in conversion yield.…”
Section: Effect Of Reaction Timementioning
confidence: 99%
“…Thus, at shorter times (3-7 min), the increase in conversion yield is mainly due to the fact that degradation/decomposition outweighs repolymerization. Then, with the prolongation of reaction time (9-11 min), degradation gradually decreased and repolymerization played the main role in liquefaction (Balat 2008;Zou et al 2009;Xie et al 2014), which attributed to the decrease in conversion yield.…”
Section: Effect Of Reaction Timementioning
confidence: 99%
“…Solvent extraction is a highly efficient way to separate different fractions from bio-oil. In previous studies, various organic solvents were used to extract phenols from HTL products, such as pentane (Putun et al 1999), tetrahydrofuran (Li et al 2013a), acetone (Zou et al 2009), toluene, methanol, diethyl ether, n-hexane, and dichloromethane (Oasmaa et al 2003;Garcia-Perez et al 2007;Sukhbaatar et al 2009;Javaid et al 2010). Li et al (2013b) extracted 12.7 wt% levoglucosan from bio-oil using water.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the condensation, cyclization, polymerization or cross-linking reactions among the light molecular fragments of SPs possible occurred to form high molecular weight compounds corresponding to the coke at higher temperature [28]. Therefore, the thermal dissolution experiments were carried out at below 320°C.…”
Section: Yields Of the Spsmentioning
confidence: 99%